PENANAMAN NILAI AGAMA DAN MORAL ANAK KELOMPOK B MELALUI BERCERITA SIROH AKHLAK NABI DI RA SYIHABUDDIN DAU KABUPATEN MALANG - Binti Khoirun Ni'mah; Khoirul Asfiyak; Yorita Febry Lismanda (Jurnal Dewantara, 2020)
Early childhood is the right time to do education. At this time the child is experiencing an extraordinary process of growth and development. Children do not have a lot of negative influences from outside or their environment. In other words, parents and educators can more easily direct children to be better. The development of children's religious and moral values is done in the learning process of telling an increase in the development of children's morals can obtain very good results. This research activity was carried out in RA Syihabuddin Dau district Malang Regency in the 2019/2020 school year. The research subjects are group B with 17 children